Optical Network Design and Planning - Simmons, Jane M. (Optical Networks, 2014)
This book takes a pragmatic approach to designing state-of-the-art optical networks for backbone, regional, and metro-core networks.   Algorithms and methodologies related to routing, regeneration, wavelength assignment, subrate-traffic grooming, and protection are presented, with an emphasis on optical-bypass-enabled (or all-optical) networks. There are numerous case studies throughout the text to illustrate the concepts, using realistic networks and traffic sets. A full chapter of economic studies offers guidelines as to when and how optical-bypass technology should be deployed. There is also extensive coverage of recent research to provide insight into how optical networks are likely to evolve. The second edition includes new chapters on dynamic optical networking and flexible/elastic optical networks. There is expanded coverage of new physical-layer technology and its impact on network design, along with enhanced coverage of ROADM architectures, including the colorless, directionless, contentionless, and gridless properties. It covers other hot topics such as software defined networking, energy efficiency, and multi-domain networks, as well as new architectural paradigms and algorithmic techniques. Numerous exercises have been added to probe the concepts in more detail and inspire directions for future research.